Peste Bubónica em Cantão (1895)
This is a consular dispatch from the Portuguese Consulate in Canton, dated 10 July 1895 (document number 11B), reporting on the sanitary conditions in Canton and surrounding areas during an outbreak of bubonic plague. The document, addressed to the Minister and Secretary of State for Royal Affairs, details the consul’s communication with the Governor of Macau regarding the epidemic. It confirms that while Canton itself was free of active plague transmission since April 1895, neighbouring populations continued to report cases. The consul notes that although local mortality remains elevated due to tropical heat and the Chinese population’s relative immunity, no confirmed bubonic plague cases have been recorded within Canton’s urban boundaries. He acknowledges persistent rumours of isolated cases but cannot verify them. Conversely, he reports that plague continues to appear in certain villages near Canton, as confirmed by local mandarins residing among Chinese communities. The document underscores the difficulty in monitoring rural outbreaks and the limitations of official reporting mechanisms. This transcription offers valuable insight into late 19th-century public health perceptions, colonial administrative responses, and the challenges of epidemic control in treaty port cities under imperial frameworks.
Keywords: Bubonic Plague Outbreak; Canton Free of Active Plague; Chinese Urban Health Perceptions; Colonial Administration Epidemic Response; Consul Communication Macau Governor; Consular Dispatch Analysis; Cross-Border Health Surveillance; Document 11B; Epidemic Containment Strategies; European Consular Reporting; Historical Epidemiology South China; Historical Public Health Perception; Imperial Diplomatic Correspondence; Isolated Cases Verification; Late 19th Century Medicine; Mandarins Local Reporting; Official Reporting Limitations; Port Cities Disease Transmission; Portuguese Consulate in Canton; Public Health Late Qing; Relative Immunity Chinese Communities; Rural Plague Monitoring; Sanitary Conditions Canton; Transcription; Transcription Consular Dispatch; Tropical Heat Disease Impact